Pengaruh Kepuasan Kerja dan Lingkungan Kerja terhadap Motivasi Kerja PNS Sekretariat DPRD Sumatera Barat - Azhari, Zahara; Syamsir, Syamsir (Fakultas Ilmu Sosial Universitas Negeri Padang, 2012)
This study aimed at analyzing the effect of job satisfaction and work environment toward work motivation among civil servants in the secretariat of Local Parliament (DPRD) of West Sumatera Province. Quantitative approach has been used in this study. Data was collected from 52 respondents of Local Parliament secretariat staffs and managers through questionnaires. The data was analyzed through multiple regression analysis by using SPSS version 15.0. The finding of this study indicated that there was a positive effect of job satisfaction and work environment toward work motivation at the levels of 19,9%. It means that 80,1% of the work motivation was affected by variables other than job satisfaction and work environment, such as, leadership style, work ethics, etc.